Isolation and characterization of potentially pathogenic Vibrio species in a temperate, higher latitude hotspot. Issue 4 (21st June 2020) - Ford, Charlotte L.; Powell, Andy; Lau, Dawn Yan Lam; Turner, Andrew D.; Dhanji‐Rapkova, Monika; Martinez‐Urtaza, Jaime; Baker‐Austin, Craig
Summary: The recent emergence of Vibrio infections at high latitudes represents a clear human health risk attributable to climate change. Here, we investigate the population dynamics of three Vibrio species: Vibrio parahaemolyticus, Vibrio vulnificus and Vibrio cholerae within a British coastal estuarine site, with contrasting salinity and temperature regimes during an intense heatwave event. Water samples were collected weekly through the summer of 2018 and 2019 and filtered using membrane filtration and subsequently grown on selective media. Suspected vibrios were confirmed using a conventional species‐specific PCR assay and further analysed for potential pathogenic markers. Results showed that Vibrio parahaemolyticus, Vibrio vulnificus and Vibrio cholerae were present at high concentrations throughout both years, with their populations at substantially greater abundances corresponding to conditions of higher water temperatures during the heatwave of 2018 and at lower salinity sites, which is comparable to the results of previous studies. A subset of strains isolated during the extreme heatwave event in 2018 (46 Vibrio parahaemolyticus, 11 Vibrio cholerae and 4 Vibrio vulnificus ) were genomically sequenced. Analysis of these 63 sequenced strains revealed a broad phenotypic and genomic diversity of strains circulating in the environment. An analysis of pathogenicity attributes identified a broad array of virulence genes across all three species, including a variety of genes associated with human disease. This study highlights the importance of the need for an increased Vibrio spp. surveillance system in temperate regions and the potential impact warming events such as heatwaves may have on the abundance of potentially pathogenic bacteria in the environment.